A Simple Way to Maintain the Top 50 Ranking Scientists in the SINTA from Excessive Self-Citations - Tole Sutikno; Herman Yuliansyah; Lina Handayani (Bulletin of Electrical Engineering and Informatics, 2018)
Top 50 authors in the Science and Technology Index (SINTA) is become popular as Indonesian top 50 ranking scientists to measure both the productivity and quality of the publications. Unfortunately, to get a high ranking in SINTA, some authors are strongly indicated that they do instant and unfair ways through citation cartels or self-citation. Based on manual investigation, excessive self-citations are conducted through publication in international conference. This paper proposed a simple way to drop abuse of excessive self-citations by categorized research articles as main publication and others as secondary publication based on Scopus database. This method is proposed to avoid perverse and unintended effects on the direction of research and publication in Indonesia.